Statics with MATLAB® - Marghitu, Dan B.; Dupac, Mihai; Madsen, Nels H. (Springer London : Imprint: Springer, 2013)
Engineering mechanics involves the development of mathematical models of the physical world. Statics addresses the forces acting on and in mechanical objects and systems. Statics with MATLAB®  develops an understanding of the mechanical behavior of complex engineering structures and components using MATLAB®  to execute numerical calculations and to facilitate analytical calculations.   MATLAB® is presented and introduced as a highly convenient tool to solve problems for theory and applications in statics. Included are example problems to demonstrate the MATLAB® syntax and to also introduce specific functions dealing with statics. These explanations are reinforced through figures generated with MATLAB® and the extra material available online which includes the special functions described. This detailed introduction and application of MATLAB® to the field of statics makes Statics with MATLAB® a useful tool for instruction as well as self study,  highlighting the use of symbolic MATLAB® for both theory and applications to find analytical and numerical solutions.